giai phuong trinh (2x+3)(x+2)2(2x+5)=3
\(\left(2x+3\right)\left(x+2\right)^2\left(2x+5\right)=3\)(Giai phuong trinh)
\(\frac{x}{2x-6}+\frac{x}{2x+2}=\frac{2x^2}{x^2+2x-3}\) giai phuong trinh lop 8
Giai phuong trinh sau
(x-2)^3 = ( 2x+1)^3
giai phuong trinh:
a)2x(x+5)-(x-3)^2 = x^2 +6
b)(4x+7)(x-5)-3x^2=x(x-1)
\(\sqrt{x+2+3\sqrt{ }2x-5}+\sqrt{x-2-\sqrt{ }2x-5}=2\sqrt{2}\) 2\(\sqrt{2}\) giai phuong trinh
giai phuong trinh x^2+2x+3=(x^2+x+1)(x^4+x^2+4)
giai phuong trinh (2x2+1)(2x+5)=(2x2+1)(x-1)
giai phuong trinh sau: \(\frac{x+2}{5}-\frac{x}{3}=\frac{2x-5}{2}\)